2018
DOI: 10.1029/2018je005540
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mars‐Relevant Soil Analogs on the Water Uptake of Magnesium Perchlorate and Implications for the Near‐Surface of Mars

Abstract: The water uptake and release by perchlorate salts have been well studied since the first in situ identification of such salts in the Martian soil by the Phoenix mission in 2008. However, there have been few studies on the effect of the insoluble regolith minerals on the interaction of perchlorate with water vapor. In this work, we investigate the impact of a Mars-relevant mineral, montmorillonite, and a Mars soil analog, Mojave Mars Simulant (MMS), on the deliquescence (transition from dry crystalline to aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Recent research has focused on the interaction of salts in the soils with atmospheric water. There have been numerous studies that suggest that sulphates, perchlorate and chloride salts in the regolith can absorb water from the atmosphere, forming hydrates, by absorption, and then liquid brines, through deliquescence and hydration [10][11][12][13][14][15][16][17][18][19][20][21][22]. Brines are aqueous saline solutions where the presence of salts decreases the freezing temperature of the solution and its saturation water vapor pressure [23], allowing it to capture water from the atmosphere when the relative humidity (RH) is higher than the threshold, which is known as deliquescence relative humidity (DRH) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has focused on the interaction of salts in the soils with atmospheric water. There have been numerous studies that suggest that sulphates, perchlorate and chloride salts in the regolith can absorb water from the atmosphere, forming hydrates, by absorption, and then liquid brines, through deliquescence and hydration [10][11][12][13][14][15][16][17][18][19][20][21][22]. Brines are aqueous saline solutions where the presence of salts decreases the freezing temperature of the solution and its saturation water vapor pressure [23], allowing it to capture water from the atmosphere when the relative humidity (RH) is higher than the threshold, which is known as deliquescence relative humidity (DRH) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Un der the con di tions mea sured by the REMS in stru ment at Gale Crater on Mars, some chlo rine-con tain ing salts can hy drate and oth ers de hy drate on daily cy cles based on lab o ra tory tests (Gough et al, 2019), how ever, at mo spher i cally based hydration of salts may be very slow. Aque ous so lu tions from the in ter ac tion of var i ous per chlor ates are ex pected to emerge around the Phoenix land ing site but not prob a ble at the Cu ri os ity land ing site of Gale crater (Primm et al, 2018); how ever, del i ques cence is expected there (Rivera Valentín et al, 2018). Ana lys ing the Phoenix land ing site, RH was usu ally <5% in the day and >95% at night-time, the tran si tion be tween the two val ues be ing rapid (Zent et al, 2016).…”
Section: Background Informationmentioning
confidence: 99%
“…Chlorine-containing salts may be enhanced at RSL locations (Ojha et al, 2015), although this has been questioned recently (Leask et al, 2018;Vincendon et al, 2019). It has been suggested that salts in the Martian soil may uptake water and then lose water during diurnal or seasonal cycles (Fischer et al, 2014;Gough et al, 2011Gough et al, , 2019Heinz et al, 2016;Nuding et al, 2014;Primm et al, 2018). This exchange of atmospheric water by salts may be due to deliquescence and efflorescence (solid-aqueous transitions) or hydration and dehydration (solid-solid transitions).…”
Section: Introductionmentioning
confidence: 99%